CORPORATE DISCLOSURE IN INDONESIA: CORPORATE GOVERNANCE PRACTICES AND OWNERSHIP STRUCTURE - Rifqy Nur Fadlillah; Iman Harymawan (Berkala Akuntansi dan Keuangan Indonesia, 2018)
This study aims to determine the effect of company disclosure after the Minister of Energy and Mineral Resources Regulation No. 7 of 2012 and Minister of Finance Regulation No. 75/PMK.011/2012 on Indonesian mining companies. The data used in this study came from mining companies listed on the Indonesia Stock Exchange in 2010-2014 with a total of 184 mining companies. The analysis technique used was multiple linear regression analysis with the help of STATA 14.0 software. Corporate Governance practices and ownership structure are variables that will be tested whether they will affect disclosure with control variables of size, ROA, and leverage. The results of the regression show that after the government regulation regarding mining companies, it can be seen that the variable of corporate governance practice and the variable of ownership structure have no influence on the amount of disclosure made by mining companies.